A STUDY OF TENSES USED IN ENGLISH ONLINE NEWS WEBSITE - Muta, Jittra; Dennis, Nutprapha (International Journal of Research -GRANTHAALAYAH, 2016)
The purposes of this study were to analyze and describe English tenses used in an online news website and to examine which types of English tenses are frequently used in an online news website. The material in this study was 20 news in Mini-Lessons from B r e a k I n g N e w s E n g l i s h .c o m. The research instrument was a checklist which determines and categorizes English tenses as past tense, present tense, and future tense. The data collections were analyzed with the frequency and percentage. The research findings of the study showed that all using of English tenses in the 20 news from the Mini-Lessons were 279 sentences; past tense were 155 sentences (56%), present tense were 120 sentences (43%), and future tense were 4 sentences (1%). The most English tenses aspect of the news were past simple tense and present tense; past simple tense, present simple tense, present perfect tense, and present progressive tense, respectively. In contrast, breaking news used the least English tenses aspect of the news was past perfect tense, future simple tense, past progressive tense, present perfect progressive tense, and future perfect tense, while there were no used past perfect progressive tense, future progressive tense, future perfect tense, and future perfect progressive tense in the 20 selected breaking news.